Treatment of condylomata acuminata - surgical excision and CO2 laser vaporization - Perišić, Svetlana (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2004)
Background. The use of different procedures for treatment of HPV depends on the viral genotype, the localization of lesions and the stage of infection. Materials and methods. Results from the treatment of 592 patients at the OB/GYN Hospital "Narodni front" (Belgrade, Serbia and Montenegro), with intraepithelial lesions of cervix, vagina and vulva caused by HPV, were evaluated. Various treatments were applied: surgical excision, CO2 laser vaporization, surgical excision followed by CO2 laser vaporization, podophyllin, interferon beta gel, cryotherapy and abrasion. Results. After three months, the comparative incidence of recurrences was as follows: the highest percentage was in the group of patients that had been treated with podophyllin, interteron beta gel, cryotherapy or abrasion (14,5%), while the lowest was in the group treated with classic surgical excision followed by CO2laser vaporization (5,77%). Conclusion. Our results show that surgical treatment followed by CO2 laser vaporization was the best treatment for condylomas of cervix, vagina and vulva.
Keywords: Condylomata Acuminata; Cryotherapy; dermatologija; Drug Therapy; ginekologija; Interferon-Beta; Kondilomata akuminata; Krioterapija; Laser Coagulation; Laserska koagulacija; papiloma virusi; Podofilin; Podophyllin; Ponovitev; Recurrence; Surgery; Therapy; Treatment Outcome; virusne bolezni; zdravljenje; Zdravljenje, izid